2010
DOI: 10.1186/cc9257
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrogen sulfide on hemodynamics, inflammatory response and oxidative stress during resuscitated hemorrhagic shock in rats

Abstract: Introduction Hydrogen sulfide (H 2 S) has been shown to improve survival in rodent models of lethal hemorrhage. Conversely, other authors have reported that inhibition of endogenous H 2 S production improves hemodynamics and reduces organ injury after hemorrhagic shock. Since all of these data originate from unresuscitated models and/or the use of a pre-treatment design, we therefore tested the hypothesis that the H 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…These results are in line with a previous observation showing that H 2 S/HSprotects against cellular aging via KEAP1/NRF2 signaling despite the absence of an effect on the expression of these proteins [42]. However, an upregulation of NRF2 upon sulfide treatment was reported in other studies [12,16].…”
Section: Discussionsupporting
confidence: 93%
“…These results are in line with a previous observation showing that H 2 S/HSprotects against cellular aging via KEAP1/NRF2 signaling despite the absence of an effect on the expression of these proteins [42]. However, an upregulation of NRF2 upon sulfide treatment was reported in other studies [12,16].…”
Section: Discussionsupporting
confidence: 93%
“…Pharmacologic adjuncts have demonstrated significant promise in minimizing metabolic and resuscitative requirements after an ischemia-reperfusion injury in swine and murine models. 5,16,17 HS is a medication of this class and is thought to work by minimizing the activation of the systemic inflammatory cascade that occurs after ischemiareperfusion injuries and allows reduction in cytotoxic inflammatory mediators and the downregulation of Lselectin expression, causing a reduced neutrophil extravasation and tissue infiltration. 5,18 Within our own laboratory, we demonstrated that valproic acid minimized aortic endothelial cell injury and resuscitative requirements with this same model when administered at the time of crossclamp.…”
Section: Discussionmentioning
confidence: 99%
“…5,16,17 HS is a medication of this class and is thought to work by minimizing the activation of the systemic inflammatory cascade that occurs after ischemiareperfusion injuries and allows reduction in cytotoxic inflammatory mediators and the downregulation of Lselectin expression, causing a reduced neutrophil extravasation and tissue infiltration. 5,18 Within our own laboratory, we demonstrated that valproic acid minimized aortic endothelial cell injury and resuscitative requirements with this same model when administered at the time of crossclamp. 4 However, for these medications to enter clinical practice, preclinical studies are essential to analyze the effect and preclinical response to novel therapeutics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations